2006
DOI: 10.1191/0960327106ht640oa
|View full text |Cite
|
Sign up to set email alerts
|

The local lymph node assay in practice: a current regulatory perspective

Abstract: Following the formal acceptance of the local lymph node assay (LLNA) as an Organization for Economic Cooperation and Development (OECD) guideline in April 2002, the UK Health and Safety Executive (HSE) informed notifiers that this was now the method of choice for the assessment of skin sensitization potential under the EU notification scheme for new industrial chemicals (NONS). This paper summarizes the experience of the HSE for the 2-year period immediately following the issuing of this statement, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The development of models for assessment of the potentials of LMW chemicals to induce allergic reactions is an important task for occupational health care professionals and the decisions they undertake establishing safe exposure limits. The local lymph node assay (LLNA) is now a validated method for assessing the potentials of chemicals to induce skin contact allergy [3][4][5][6]. However, until now, there is no validated method to assess the potentials of chemicals to induce respiratory sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The development of models for assessment of the potentials of LMW chemicals to induce allergic reactions is an important task for occupational health care professionals and the decisions they undertake establishing safe exposure limits. The local lymph node assay (LLNA) is now a validated method for assessing the potentials of chemicals to induce skin contact allergy [3][4][5][6]. However, until now, there is no validated method to assess the potentials of chemicals to induce respiratory sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Woolhiser MR assessed the response of chemical sensitizers in the LLNA across 6 strains of female mice, and concluded that "DBA/2, B6C3F1 and BALB/c mice are good choices for continued evaluation as additional mouse strains for use in the LLNA" (Woolhiser et al, 2000). Other studies also showed that BALB/c mice may have small differences compared with CBA mice (Cockshott et al, 2006;Guo et al, 2013). Since the OECD guidelines state that "other strains and males may 2.74 a Values are expressed as the mean ± S.D.…”
Section: Discussionmentioning
confidence: 99%
“…After the formal validation of the assay, some groups thought that it may be too sensitive and/or prone to false positives [53,54] . This topic has been extensively discussed in the literature [41,[54][55][56][57] . It is a fact that any toxicology assay has both false positives and false negatives, and the LLNA is no exception.…”
Section: Guinea Pig Modelsmentioning
confidence: 99%